Social and environmental reporting and its role in maintaining or creating organizational legitimacy - Deegan, Craig (Accounting, auditing & accountability journal ;, 2002)
This article has been written to provide an overview of a particular theoreticalperspective that has been used to explain why managers might elect to publiclydisclose information about particular aspects of their social or environmentalperformance[1].